Epidemiological trends in skin cancer - Zoe Apalla; Aimilios Lallas; Elena Sotiriou; Elizabeth Lazaridou; Demetrios Ioannidis (Mattioli1885, 2017)
Skin cancer, including melanoma and non-melanoma skin cancer (NMSC), represents the most common type of malignancy in the white population. The incidence rate of melanoma is increasing worldwide, while the associated mortality remains stable, or is slightly decreasing. On the other hand, the incidence for NMSC varies widely, with the highest rates reported in Australia. In the current review, we highlight recent global trends in epidemiology of skin cancer. We discuss controversial issues raised in current epidemiological data, we analyze the most important risk factors associated with the development of melanoma and NMSC and the impact of skin cancer on health care services. Furthermore, we underline the pressing need for improved registration policies, especially for NMSC, and lastly, we refer to the ongoing primary and secondary prevention strategies and their outcomes so far.